A 1-aminocyclopropane-1-carboxylic-acid (ACC) dipeptide elicits ethylene responses through ACC-oxidase mediated substrate promiscuity - Vaughan-Hirsch, John; Li, Dongdong; Roig Martinez, Albert; Roden, Stijn; Pattyn, Jolien; Taira, Shu; Shikano, Hitomi; Miyama, Yoko; Okano, Yukari; Voet, Arnout; Van de Poel, Bram (Frontiers in Plant Science, 2022)
Plants produce the volatile hormone ethylene to regulate many developmental processes and to deal with (a)biotic stressors. In seed plants, ethylene is synthesized from 1-aminocyclopropane-1-carboxylic acid (ACC) by the dedicated enzyme ACC-oxidase (ACO). Ethylene biosynthesis is tightly regulated at the level of ACC through ACC synthesis, conjugation and transport. ACC is a non-proteinogenic amino acid, which also has signaling roles independent from ethylene. In this work, we investigated the biological function of an uncharacterized ACC dipeptide. The custom-synthesized di-ACC molecule can be taken up by Arabidopsis in a similar way as ACC, in part via Lysine Histidine Transporters (e.g. LHT1). Using Nano-Particle Assisted Laser Desoprtion/Ionisation (Nano-PALDI) mass-spectrometry imaging, we revealed that externally fed di-ACC predominantly localizes to the vasculature tissue, despite it not being detectable in control hypocotyl segments. Once taken up, the ACC dimer can evoke a triple response phenotype in dark-grown seedlings, reminiscent of ethylene responses induced by ACC itself, albeit less efficiently compared to ACC. Di-ACC does not act via ACC-signaling, but operates via the known ethylene signaling pathway. In vitro ACO activity and molecular docking showed that di-ACC can be used as an alternative substrate by ACO to form ethylene. The promiscuous nature of ACO for the ACC dimer also explains the higher ethylene production rates observed in planta, although this reaction occurred less efficiently compared to ACC. Overall, the ACC dipeptide seems to be transported and converted into ethylene in a similar way as ACC, and is able to augment ethylene production levels and induce subsequent ethylene responses in Arabidopsis.